The socialists and private education from the Debré Law (1959) - Ferhat, Ismail; Poucet, Bruno (Historia y Memoria de la Educación, 2016)
For the French Socialists, laicism (understood as the strict separation of State from religion) is a key issue, both in its programs and in the public policies they promote. It was precisely in the realm of the school that this specific relationship between this political trend and this notion was established. But in 1959, Michel Debré’s government passed a law (named after him) that opened the right to public funding to private schools, predominantly Catholic. This has raised complex reactions from the Socialists since the vote of that legal text until today. In effect, from their position in the opposition until 1981, first they promised to repeal the Debré Law and to nationalize those private schools funded by the state. Since the eighties, and from their position and experience of power in the government, the Socialists have stepped back from the project, preferring to seek a compromise with Catholic schools. Since the beginning of the 21st century, the issue of development of other private denominational schools (Jewish, Muslim, Protestant evangelicals, traditionalist Catholics) has come back to stimulate debate among socialists.